N-nitrosodiethylamine induced redox imbalance in rat liver: Protective role of polyphenolic extract of Blighia sapida arilli - Oloyede, O.B.; Ajiboye, T.O.; Komolafe, Y.O. Komolafe (Free Radicals and Antioxidants)
Aim: This study investigates the reactive oxygen species detoxification potentials of polyphenolic extract of Blighia sapida arilli in the liver of N-nitrosodiethylamine-treated rats. Methods: Male rats, weighing 158 2.9 g were completely randomized into 7 groups (AeG) of five rats each. Rats in C, D, E and F were administered orally once daily at 24 h interval for 7 days with 1000, 250, 500 and 1000 mg/kg body weight of polyphenolic extract of B. sapida arilli respectively. Group G was given 100 mg/kg body weight of vitamin C. On the sixth day, group B, D, E, F and G were administered with 100 mg/kg body weight N-nitrosodiethylamine (NDEA). Group A, which served as the control was treated like the test groups except, that the animals received distilled water only. Results: Reactive oxygen species detoxifying enzymes (superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase and glucose 6-phosphate dehydrogenase) activities were significantly (P < 0.05) induced by B. sapida arilli. These inductions significantly (P < 0.05) attenuated the decrease in reactive oxygen species detoxifying enzymes mediated by NDEA treatment and compared favourably with vitamin C. NDEA-mediated elevation in the concentrations of oxidative stress biomarkers; malondialdehyde, conjugated dienes, lipid hydroperoxides, protein carbonyl and percentage DNA frag- mentation were significantly (P < 0.05) lowered by polyphenolic extract of B. sapida arilli. Conclusion: Overall, the results obtained from this study revealed that the polyphenolic extract from B. sapida arilli enhanced the detoxification of reactive oxygen species in NDEA-treated rats. The poly- phenols also prevented the peroxidation of lipid, oxidation of proteins as well as fragmentation of DNA component in the liver of rats and hence gave the evidence of possible prophylactic potentials of B. sapida arilli.
Keywords: Blighia sapida; Polyphenols; Reactive oxygen species; Antioxidants; Free radicals